Determinants of Sustainable Growth of SMEs in Developing Countries: The Case of Ethiopia - Gemechu Abdissa; Abebe Ayalew; Anna Dunay; Csaba Bálint Illés (Economies, 2022)
Small and medium-sized businesses (SMEs) played a significant role in domestic employment and inclusive GDP in developing countries such as Ethiopia. Accordingly, the purpose of this study is to investigate the determinants of sustainable growth of SMEs in developing countries, notably in Ethiopia. To achieve the objectives of this study, both descriptive and explanatory research designs were used. In addition to this, primary data was collected from SMEs engaged in service, manufacturing, trade, construction, and urban agriculture. The sampling techniques used for this study is the stratified simple random sampling technique in which 194 employees of SMEs were drawn as a sample size for this study. Moreover, multiple linear regression models were used with the Statistical Package for the Social Sciences (SPSS) version 23 software as the data analysis tool. According to the study’s findings, crucial issues such as the coronavirus and political uncertainty in Ethiopia, which have allowed for widespread corruption, are now harming the growth of SMEs. According to the findings, political instability, corruption, and COVID-19 are now having a substantial effect on the growth of SMEs in Ethiopia. These concerns have serious consequences for the long-term sustainability of Ethiopian SMEs. Hence, the study strongly advocates for sequential policy reform in the region, as well as a review of current policies aimed at ensuring effective corruption control in the region and bringing political stability to the region, particularly in Ambo town, Ethiopia.